Simultaneous circulation of genotypes I and III of dengue virus 3 in Colombia (2008)
ABSTRACT: Background: Dengue is a major health problem in tropical and subtropical regions. In Colombia, dengue viruses (DENV) cause about 50,000 cases annually, 10% of which involve Dengue Haemorrhagic Fever/Dengue Shock Syndrome. The picture is similar in other surrounding countries in the Americas, with recent outbreaks of severe disease, mostly associated with DENV serotype 3, strains of the Indian genotype, introduced into the Americas in 1994. Results: The analysis of the 3'end (224 bp) of the envelope gene from 32 DENV-3 strains recently recovered in Colombia confirms the circulation of the Indian genotype, and surprisingly the co-circulation of an Asian-Pacific genotype only recently described in the Americas. Conclusion: These results have important implications for epidemiology and surveillance of DENV infection in Central and South America. Molecular surveillance of the DENV genotypes infecting humans could be a very valuable tool for controlling/mitigating the impact of the DENV infection.